2008
DOI: 10.1080/00365590801933226
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of a urotherapy training program in children with functional urinary incontinence: A 2-year follow-up

Abstract: Compared with the published data on the natural course of incontinence, the urotherapy program evaluated in this study resulted in higher success rates. Compared with 6-month follow-up, improvement rates proved to be stable, and cure rates (with the exception of patients with night-time wetting in the outpatient training group) even increased significantly during the 2-year follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 23 publications
0
16
0
2
Order By: Relevance
“…The efficacy of (daytime) urotherapy in nocturnal enuresis is, however, still unproven, because of a lack of prospective, controlled trials [26]. Bladder distention exercises have, however, recently been shown to be useless as a therapy for nocturnal enuresis, even if they succeed in increasing voided volumes [27].…”
Section: Detrusor Overactivity Treatmentmentioning
confidence: 99%
“…The efficacy of (daytime) urotherapy in nocturnal enuresis is, however, still unproven, because of a lack of prospective, controlled trials [26]. Bladder distention exercises have, however, recently been shown to be useless as a therapy for nocturnal enuresis, even if they succeed in increasing voided volumes [27].…”
Section: Detrusor Overactivity Treatmentmentioning
confidence: 99%
“…It has been demonstrated that solely application of the standard urotherapy is resulting with an improvement almost in 80% of the children [914]. Therefore, regardless of the type of the LUTD, this bladder training programme is considered to be mandatory before starting any specific interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Obwohl die Anfänge der Blasenschulungskonzepte in Skandinavien bereits in die späten 1980er Jahre zurückreichen, existiert bis heute lediglich eine geringe Anzahl an Evaluationsstudien zur Durchführung von Blasenschulungen [2,3,10,14,18,19] …”
Section: Originalien Hintergrund Und Fragestellungunclassified
“…Erste Hinweise auf stabile Therapieerfolge durch teilstationäre bzw. stationäre Blasenschulungen über 2 Jahre hinweg lieferten Bachmann et al [3].…”
unclassified